Hibernating Myocardium - Arafath, Mohamed Yaser; Singh, Lokesh; Debi, Uma; Singhal, Manphool; Sood, Ashwani; Kumar, Rohit Manoj (Cardiology and Cardiovascular Medicine, 2021)
Hibernating myocardium is important sequelae of ischemic heart disease causing reversible cause of morbidity in the form of systolic dysfunction. LV dysfunction need not always represent dead myocardium. Differentiation between viable and non-viable myocardium has to be accurate for proper planning of the further management of the patients with post ischemic left ventricular dysfunction.